THE DIFFICULTY LEVEL FOR THE READING TEXTS OF SMA PELITA RANTEPAO - Nehru P. Pongsapan (AgroSainT, 2010)
In grading and selecting the teaching materials for reading, there is a tendency that teachers just refer to the levels as elementary, intermediate, and advance. They tend not to pay attention to the proficiency of the learners. Consequently, the achievement of the learners in reading course is low or high, because the materials are too easy or difficult for them. That is why a teacher must be able to select suitable materials in accordance with his learners’ interest, fluency and comprehension. Based on the background above, the problems of this study can be formulated as follows: What is the difficulty level of the reading texts for the second year students of SMA Pelita Rantepao ? The research objective is to find out the difficult levels of the reading texts for the second year students of SMA Pelita Rantepao. The finding of this research will provide useful information, which is expected to be beneficial or give contribution to the users as well as the government and syllabus designer to teach reading texts. Research method used to this research is descriptive. The indicators that have been used to measure the difficulty level of reading text for the second year students of SMA Pelita Rantepao are as follows: If the mean score obtained by the students less than 44 per cent, the text is described as being at the Frustrational reading level, between 44 to 53 percent, the text is described as being at the Instructional reading level, and over 53 per cent, the text is described as being at the Independence reading level. The population of the research is the second year student of SMA Pelita Rantepao academic year 2009/2010. They consist of 97 students. therefore the writer took 30 students randomly as sample. To analyze the data, the writer used mean percentage technique. The result of 30 students is 42.11% and falls into Frustrational Level. The difficulty level of the reading text for the second year students of SMA Pelita Rantepao falls into frustrational reading level. It means that the reading text is very difficult for the students.